2009
DOI: 10.1002/glia.20867
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of sPLA2 following spinal cord injury and a functional role for sPLA2‐IIA in mediating oligodendrocyte death

Abstract: After the initial mechanical insult of spinal cord injury (SCI), secondary mediators propagate a massive loss of oligodendrocytes. We previously showed that following SCI both the total phospholipases activity and cytosolic PLA2-IVα protein expression increased. However, the expression of secreted isoforms of PLA2 (sPLA2) and their possible roles in oligodendrocyte death following SCI remains unclear. Here we report that mRNAs extracted 15 min, 4 hr, 1 day, or 1 month after cervical SCI show marked upregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 81 publications
(116 reference statements)
1
48
0
Order By: Relevance
“…We have not detected sPLA 2 GIIA expression in the naive uninjured spinal cord , suggesting that the presence of sPLA 2 activity reported earlier is attributable to other forms of sPLA 2 expressed constitutively for normal physiological functions (Titsworth et al 2009). sPLA 2 activity has been shown to be increased after spinal cord trauma (Liu et al 2006), and we have reported that sPLA 2 GIIA expression is induced during the first week after SCI, peaking at day 3 and appearing mainly in oligodendrocytes and astrocytes and in a small proportion in neurons and microglia/macrophages ).…”
Section: Pla 2 Superfamilymentioning
confidence: 88%
See 3 more Smart Citations
“…We have not detected sPLA 2 GIIA expression in the naive uninjured spinal cord , suggesting that the presence of sPLA 2 activity reported earlier is attributable to other forms of sPLA 2 expressed constitutively for normal physiological functions (Titsworth et al 2009). sPLA 2 activity has been shown to be increased after spinal cord trauma (Liu et al 2006), and we have reported that sPLA 2 GIIA expression is induced during the first week after SCI, peaking at day 3 and appearing mainly in oligodendrocytes and astrocytes and in a small proportion in neurons and microglia/macrophages ).…”
Section: Pla 2 Superfamilymentioning
confidence: 88%
“…However, of 14 mammalian PLA 2 s analyzed, only cPLA 2 GIVA, iPLA 2 VIA, and sPLA 2 IIA are significantly up-regulated at the mRNA level after SCI (Table 2; Liu et al 2006;Titsworth et al 2009;López-Vales et al 2011). Emerging evidence indicates an important role for members of the PLA 2 superfamily in secondary tissue damage and in tissue protection after SCI.…”
Section: Pla 2 Superfamilymentioning
confidence: 92%
See 2 more Smart Citations
“…sPLA 2 -IIA plays a role in nociception from the paw and orofacial region [20,21] and may contribute to neuronal injury in acute and chronic neurodegenerative diseases. sPLA 2 -IIA activity and expression are upregulated after cerebral ischemia [22,23] and spinal cord injury [24] . Enzyme expression is increased in Alzheimer's disease, especially in regions containing amyloid-␤ plaques [25] .…”
Section: Introductionmentioning
confidence: 99%